2015
DOI: 10.1093/neuonc/nov218.07
|View full text |Cite
|
Sign up to set email alerts
|

Imct-07therapeutic Outcomes of Intrathecal Interleukin-2 in Metastatic Melanoma Patients With Leptomeningeal Disease (Lmd)

Abstract: BACKGROUND: Melanoma patients with LMD have a median survival of 1.8 months; there is significant medical need for innovative therapeutic strategies. METHODS: Stage IV melanoma patients were diagnosed with LMD by positive CSF cytology and/or leptomeningeal enhancement on post-contrast MRI. Patients received treatment with 1-5 doses/week of intrathecal IL-2 (IT IL2) for 4 weeks, followed by weekly injections for 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…33 Intrathecal IL-2 has been administered safely in melanoma patients with LMD, and in some patients has resulted in clinical responses and prolonged survival. 3,34,35 A clinical trial is currently open to evaluate intrathecal treatment with ACT, with a previous case report supporting the safety and feasibility of this approach. 36 There is a critical unmet need to develop new therapeutic strategies and clinical trials for patients with LMD.…”
Section: Leptomeningeal Diseasementioning
confidence: 99%
“…33 Intrathecal IL-2 has been administered safely in melanoma patients with LMD, and in some patients has resulted in clinical responses and prolonged survival. 3,34,35 A clinical trial is currently open to evaluate intrathecal treatment with ACT, with a previous case report supporting the safety and feasibility of this approach. 36 There is a critical unmet need to develop new therapeutic strategies and clinical trials for patients with LMD.…”
Section: Leptomeningeal Diseasementioning
confidence: 99%
“…62,63 A recent report details a study in which IL-2 was administered intrathecally at 1-5 doses/week for four weeks, then weekly for four weeks, then every other week followed by monthly. 64 Although the data have not reached maturity, responses were seen in patients with LMM. A median survival of 9.1 months was reported with 16% of patients showing a median survival of >24 months.…”
Section: Clinical Experience With Immune Therapies In Lmmmentioning
confidence: 97%
“…A number of cases have reported complete responses to IL‐2 in patients with MBM, raising interest in its potential use in LMM . A recent report details a study in which IL‐2 was administered intrathecally at 1–5 doses/week for four weeks, then weekly for four weeks, then every other week followed by monthly . Although the data have not reached maturity, responses were seen in patients with LMM.…”
Section: Clinical Experience With Immune Therapies In Lmmmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported on 42 participants with melanoma-associated leptomeningeal metastasis who were treated with 1 to 5 doses of intrathecal IL-2 every week for 4 weeks, followed by weekly injections for 4 weeks, and then every other week. 35 The study patients continued to receive single-injection maintenance doses every 1 to 3 months. A median survival rate of 9.1 months (range, 0.7-86.2) was reported, and 16% of study patients had an overall survival of more than 24 months.…”
Section: Intrathecal Interleukinmentioning
confidence: 99%